Emissions of heating appliances fuelled with agropellet produced from vine pruning residues and environmental aspects. (June 2018) - Pizzi, A.; Foppa Pedretti, E.; Duca, D.; Rossini, G.; Mengarelli, C.; Ilari, A.; Mancini, M.; Toscano, G.
Abstract: Vine is one of the most widespread crop cultivated in Italy. The management of these residues is linked to an additional cost for the operator and determines environmental issues mainly due to open field combustion. A better exploitation of these residues could be the use for thermal energy production in residential heating devices fuelled with pellet. In the present work vineyard pruning residues were collected, pelletised, then characterised according to the standard for solid biofuels. Combustion tests were performed in a 150 kWth boiler fuelled with pruning pellet and the related TSP, CO, NOx emissions were measured. In order to make a comparison with the open field combustion emissions of the vineyard pruning residues, simulation tests were conducted at lab scale. Open field emissions are up to 120 times for CO emission and 30 times for TSP more than the boiler emission. Results highlighted that by avoiding open field combustion and using this residual biomass for energy production, a significant reduction of environmental pollution together with an increase in renewable energy production can be obtained. The results can be useful as support for policy makers engaged in developing the strategy for the promotion of renewable energy and air quality improvement. Highlights: Raw vineyard pruning residues and their pellet were characterised as solid biofuels. Combustion tests with vineyard residues pellet were carried out on 150kWth boiler. Open field combustion of vineyard residues were simulated at lab scale. Open field combustion emits up to 120 times CO and 30 times TSP more than boiler. In Italy open field vineyard pruning combustion can emit 137 kt CO and 13.7 kt TSP.